Differences In High Sensitivity C-Reactive Protein (Hs-Crp) Levels between Active Smokers and Passive Smokers - Seftika Dwi Niaga; Hari Saktiningsih (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2024)
Background: Background: High Sensitivity C-Reactive Protein (hs-CRP) is an acute-phase protein produced in the liver in response to inflammation, involving the immune system, blood vessels, and cardiovascular. Purpose: This study aimed to compare hs-CRP levels between active and passive smokers. Methods: This type of research is a quantitative research using a cross-sectional research design and purposive sampling techniques. This study involved 9 active smoker respondents and 9 passive smoker respondents from a population of 24 people in N Village RT 01 RW 04, Bulukerto District, Wonogiri Regency. Results: The results showed that the average hs-CRP level in active smokers was 2.51 mg/L, while in passive smokers it was 0.89 mg/L. The minimum and maximum levels of hs-CRP in active smokers were 0.90 to 4.10 mg/L, while in passive smokers it was 0.30 to 1.80 mg/L (p value 0.024<0.05). Conclusions: There was a significant difference in hs-CRP levels between active smokers and passive smokers.